Chinese visions of progress, 1895 to 1949 - Fröhlich, Thomas 1966-; Schneider, Axel ca. 20./21. Jh (Brill, 2020)
"Chinese Visions of Progress, 1895 to 1949 offers a panoramic view of reflections on progress in modern China. Since the turn of the twentieth century, the discourses on progress shape Chinese understandings of modernity and its pitfalls. As this in-depth study shows, these discourses play a pivotal role in the fields of politics, society, culture, as well as philosophy, history, and literature. It is therefore no exaggeration to say that the Chinese ideas of progress, their often highly optimistic implications, but also the criticism of modernity they offered, opened the gateway for reflections on China's past, its position in the present world, and its future course."
Includes index
Keywords: Geschichte 1895-1949; Diskurs; Fortschritt -- Motiv; China; China / Intellectual life / 20th century; Civilization, Modern / 20th century / Philosophy; Intellectuals / China / History / 20th century; Progress / Public opinion; Public opinion / China / History / 20th century; China / Civilization / Western influences; Civilization, Modern / Philosophy; Civilization / Western influences; Intellectual life; Intellectuals; Public opinion; 1900-1999; History; Konferenzschrift -- Erlangen